An efficient three-dimensional dynamic contact model for cylindrical gear pairs with distributed tooth flank errors. (October 2020) - Yuan, Bing; Chang, Lehao; Liu, Geng; Chang, Shan; Liu, Lan; Shen, Yunbo
Abstract: Coupled loaded tooth contact analysis (LTCA) model and lumped-parameters model, an efficient three-dimensional dynamic contact model for cylindrical gear pairs with distributed tooth flank errors is established. The solution scheme of the proposed model is constructed using a combination of the loaded tooth contact algorithm and the Newmark integration method. The dynamic load distributions at different input speeds can be determined, and the dynamic time-dependent mesh stiffness and dynamic composite mesh error are proposed and calculated. The proposed model is validated by comparing the obtained numerical results with the experimental results from the published works, and has much higher efficiency compared with three-dimensional dynamic contact finite element method. The effects of helix angle, mesh damping, distributed tooth flank errors and output torque on the vibration behaviors and dynamic load distributions of cylindrical gear pairs under different working conditions are investigated and discussed. The proposed model can also be used to predict the vibration behaviors and the instantaneous three-dimensional dynamic contact state of cylindrical gear pairs with different distribution forms of tooth flank errors and various tooth surface modifications.